From Victory to Vichy: Veterans in Interwar France - Chris Millington (Manchester University Press, 2012)
This book is the most up-to-date English-language study of the French veterans of the First World War. It explores the politics and associational culture of France's two largest veterans' associations between the wars, the Union federale (UF) and the Union nationale des combattants (UNC). Based on extensive research, the book argues contrary to the established historiography that the French anciens combattants were a threat to democracy. Duriing the troubled interwar years, the veterans' associations sought to extend their influence into the non-veteran milieu through public demonstrations, propaganda campaigns and the foundation of auxiliary groups. By the end of the 1930s the UF and the UNC were campaigning for an authoritarian reform of the state that foreshadwoed the Vichy regime of the war years.